CURRENT TRENDS IN THE PROFESSIONAL DEVELOPMENT OF CIVIL SERVANTS - N. A. Chetverikova (Publishing House of the State University of Management, 2019)
The professional development of state civil servants is an important part of state policy, and this process has been already sufficiently regulated by the regulatory legal acts of the Russian Federation. Therefore, at the present stage, it is necessary to develop such a system for training civil servants, that would take into account all the existing potential of the personality of a civil servant. In the process of professional development, it is necessary to take into account, that the professional activity of an official has a number of specific features, and not every individual can meet the requirements of public service as a public institution. The current studies on the professional development of civil servants have been considered in the article, the authors` vision on the issue of improving the professionalism of those, who connect their activities with serving the state, has been presented.